(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This study aims to develop a comprehensive professional development program to help general education teachers integrate digital learning platforms into the teaching and learning process using the ADDIE instructional design model. The program is structured around the five key phases of the ADDIE model - Analysis, Design, Development, Implementation, and Evaluation - providing a systematic framework for effective digital platform integration. The training program focuses on equipping teachers with the necessary skills to select, implement, and evaluate digital tools in various instructional contexts. The program development process considers best practices in instructional design and technology-enhanced learning while addressing teachers’ pedagogical needs. Special emphasis is placed on fostering engagement, adaptability, and practical application of digital resources in blended and online learning environments. By aligning professional development with the ADDIE model, this study provides a structured approach to supporting teachers in effectively utilizing digital platforms for instructional purposes. Future research will focus on piloting the program and assessing its impact on teachers' digital competencies and classroom practices.